2017
DOI: 10.1152/jn.00261.2016
|View full text |Cite
|
Sign up to set email alerts
|

Functional role of airflow-sensing hairs on the bat wing

Abstract: Bat wings are adaptive airfoils that enable demanding flight maneuvers. The bat wing is sparsely covered with sensory hairs, and wing-hair removal results in reduced flight maneuverability. Here, we report for the first time single-neuron responses recorded from primary somatosensory cortex to airflow stimulation that varied in amplitude, duration, and direction. The neurons show high sensitivity to the directionality of airflow and might act as stall detectors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…The membrane of bat wings is sparsely lined with microscopic hairs, which are associated with a variety of tactile receptors, including lanceolate receptors and Merkel cell neurite complexes [ 9 , 62 ]. It was found that two different species of bats, Eptesicus fuscus (big brown bat) and Carollia perspicillata (short-tailed fruit bat), altered their flight behavior in an obstacle avoidance task following wing hair depilation.…”
Section: Mechanosensory Feedback For Coordinated Locomotionmentioning
confidence: 99%
See 2 more Smart Citations
“…The membrane of bat wings is sparsely lined with microscopic hairs, which are associated with a variety of tactile receptors, including lanceolate receptors and Merkel cell neurite complexes [ 9 , 62 ]. It was found that two different species of bats, Eptesicus fuscus (big brown bat) and Carollia perspicillata (short-tailed fruit bat), altered their flight behavior in an obstacle avoidance task following wing hair depilation.…”
Section: Mechanosensory Feedback For Coordinated Locomotionmentioning
confidence: 99%
“…They found that E. fuscus and C. perspicillata made wider turns around obstacles and increased their flight speed after depilation, respectively [ 58 ]. These findings suggest that wing hairs act as airflow sensors that prevent stall [ 9 , 58 ].…”
Section: Mechanosensory Feedback For Coordinated Locomotionmentioning
confidence: 99%
See 1 more Smart Citation
“…This gives a sense of the structure of the hair cells, i.e., they are 3D tapering cylinders. The receptors at the end of these hair cells are involved in sensing airflow in a directional pattern, even reverse, and turbulent airflow …”
Section: D Sensing Examples In Naturementioning
confidence: 99%
“…Bats have ultrasensitive airflow sensory organs on their wing membranes characterized by flexible, elastic, and thin properties to detect airflow condition for smooth flight. [33,34] In the sensory system, the fine hairs embedded in wing membranes can sensitively capture the tiny airflow variation and experience reversible mechanical bending displacement to rapidly trigger the Merkel cells (a slow adapting mechanoreceptor that responds to gentle touch) around the hair follicles, resulting in action current that is transmitted through nerve fibers to the central nervous system to percept airflow (Figure 1a). [35,36] The simple and effective evolved sensory structures have inspired us to design a highly sensitive and adaptive airflow sensor based on microspring effect, which is enabled by well-designed graphene/single-walled nanotubes (SWNTs)-Ecoflex membrane (GSEM).…”
Section: Introductionmentioning
confidence: 99%